2017
DOI: 10.3389/fnagi.2017.00400
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Research Study of Cognitive Dysfunction and Affective Impairment after Isolated Brainstem Stroke

Abstract: Although the function of the cerebellum in neurocognition has been well-documented, the similar role of the brainstem has yet to be fully elucidated. This clinical research study aimed to combine data relating to neuropsychological assessments and P300 to explore cognitive dysfunction and affective impairment following brainstem stroke. Thirty-four patients with isolated brainstem stroke and twenty-six healthy controls were recruited; for each patient, we collated data pertaining to the P300, Addenbrooke's Cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
13
0
4
Order By: Relevance
“…DS are commonly used to test memory storage capabilities and numerical skills associated with the functioning of operational verbal memory [ 50 ]. All these tests have been utilized to assess cognitive/neuropsychological functions in Chinese population [ 51 , 52 ]. However, there is rarely systematic analysis of the consistency among these tests.…”
Section: Discussionmentioning
confidence: 99%
“…DS are commonly used to test memory storage capabilities and numerical skills associated with the functioning of operational verbal memory [ 50 ]. All these tests have been utilized to assess cognitive/neuropsychological functions in Chinese population [ 51 , 52 ]. However, there is rarely systematic analysis of the consistency among these tests.…”
Section: Discussionmentioning
confidence: 99%
“…A 2-year longitudinal study investigating the brainstem volume showed an atypical development in children and adolescents with ASD compared to matched controls, characterized by an increase of GM brainstem volume over time (Jou et al, 2013). Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume. Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume.…”
Section: Introductionmentioning
confidence: 99%
“…Further, both quantitative and qualitative sex differences have been detected in the neuroanatomy of children (Retico et al, 2016) and adults (Ecker et al, 2017) with ASD, and the brainstem is part of such sexually dimorphic brain regions (Lai et al, 2013). Moreover, recent lesion studies suggested an involvement of the brainstem in neurocognition (D'Aes et al, 2015), and specifically a cognitive dysfunction after brainstem damage (Fu et al, 2017): thus, it is crucial to analyze the impact of IQ level on brainstem volume. None of the previous studies on brainstem structural MRI in ASD individuals has addressed this issue, and more broadly low-functioning children have been neglected in neuroanatomical autism research (Jack & Pelphrey, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] In the study by Fu et al ., data from 34 patients with isolated brainstem infarction revealed that mild cognitive impairment (MCI) was noted in all, and that visuospatial, attention, linguistic, and emotional disturbances may occur after an isolated brainstem stroke. [ 9 ] Garrad et al . have reported that in seven consecutive patients referred to a neurological rehabilitation unit with lesions limited to brain stem structures, all were shown to exhibit deficits in at least one domain of cognition.…”
Section: Discussionmentioning
confidence: 99%